Efek LKS IPA bermuatan literasi saintifik tema kesehatan pencernaan dalam model pembelajaran kontekstual adaptif pada hasil belajar siswa kelas VIII SMPN 7 Padang - Putri Angjelina; Asrizal Asrizal (Universitas Negeri Padang, 2019)
Education is one of the factors that has a major influence in the progress of the 21st century. The government's efforts to deal with the challenges of the 21st century are to cultivate the school literacy movement. In addition, the government also seeks to improve learning outcomes by implementing Integrated Science learning in junior high schools. Real conditions in the field it seems that of Integrated Science learning outcomes are still relatively low. The right solution to the problem is to use Integrated science student worksheet with scientific literacy. The purpose of this study was to determine the results of research using science science student worksheet with scientific literacy as the theme of digestive health in class VIII adaptive learning contextual learning model at 7th Public Middle School in Padang. This type of research is a quasi-experimental research. The research design used was Posttest-Only Nonequivalent Control Group Design. The population in this research were all eighth grade students. The sample in this research was class VIII 2 as the experimental class and VIII 3 as the control class obtained by purposive sampling technique and cluster random sampling. The instruments used to collect data are observation sheets to assess attitudes, test sheets allocated to knowledge, and scientific performance sheets for skills competencies. The results of the research were obtained after analyzing the data with descriptive statistical analysis and two average trials. The application of Science student worksheet with scientific literacy in the adaptive contextual learning model of digestive health is related to differences in student learning outcomes with a 95% confidence level. This means that the Science student worksheet with scientific literacy in the adaptive contextual learning model of digestive health has an effect on the results of class VIII of SMP 7 Padang. So, applying the Science Literacy student worksheet is effectively applied in Integrated Science learning.